The influence of motherhood on neural systems for reward processing in low income, minority, young women. (April 2016) - Moses-Kolko, Eydie L.; Forbes, Erika E.; Stepp, Stephanie; Fraser, David; Keenan, Kate E.; Guyer, Amanda E.; Chase, Henry W.; Phillips, Mary L.; Zevallos, Carlos R.; Guo, Chaohui; Hipwell, Alison E.
Highlights: We compared neural reward responses between postpartum and nulliparous women. Ventral striatal response was related to depression and late adolescence stress. Motherhood status had no impact upon ventral striatal responses. Future study should examine motherhood effects on neural response to social reward. Abstract: Objective: Given the association between maternal caregiving behavior and heightened neural reward activity in experimental animal studies, the present study examined whether motherhood in humans positively modulates reward-processing neural circuits, even among mothers exposed to various life stressors and depression. Methods: Subjects were 77 first-time mothers and 126 nulliparous young women from the Pittsburgh Girls Study, a longitudinal study beginning in childhood. Subjects underwent a monetary reward task during functional magnetic resonance imaging in addition to assessment of current depressive symptoms. Life stress was measured by averaging data collected between ages 8–15 years. Using a region-of-interest approach, we conducted hierarchical regression to examine the relationship of psychosocial factors (life stress and current depression) and motherhood with extracted ventral striatal (VST) response to reward anticipation. Whole-brain regression analyses were performed post-hoc to explore non-striatal regions associated with reward anticipation in mothers vs nulliparous women. Results: Anticipation of monetary reward was associated with increased neural activity in expected regions including caudate, orbitofrontal, occipital, superior and middle frontal cortices. There was no main effect of motherhood nor motherhood-by-psychosocial factor interaction effect on VST response during reward anticipation. Depressive symptoms were associated with increased VST activity across the entire sample. In exploratory whole brain analysis, motherhood was associated with increased somatosensory cortex activity to reward (FWE cluster forming threshold p < 0.001). Conclusions: These findings indicate that motherhood is not associated with reward anticipation-related VST activity nor does motherhood modulate the impact of depression or life stress on VST activity. Future studies are needed to evaluate whether earlier postpartum assessment of reward function, inclusion of mothers with more severe depressive symptoms, and use of reward tasks specific for social reward might reveal an impact of motherhood on reward system activity.